2019
DOI: 10.1371/journal.pone.0218870
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and sleep problems in homeless adults

Abstract: Background For the estimated 554,000 homeless individuals on any given night in the United States, obtaining quality sleep is often challenging. This group is known to have multiple health disparities, potentially affected by sleep problems; therefore, identifying lifestyle factors–such as physical activity–that are associated with improving both quality and quantity of sleep has important implications for public health. Here, we examine associations of physical activity with subjective sleep prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Nevertheless, the relationship between physical activity and sleep remains unclear. Several studies found more physical activity has no or even a negative relation to sleep quality (Kakinami et al, 2017;Taylor et al, 2019). Further research is necessary in large populations to answer these questions.…”
Section: Clustering Of Health Risk Behaviorsmentioning
confidence: 99%
“…Nevertheless, the relationship between physical activity and sleep remains unclear. Several studies found more physical activity has no or even a negative relation to sleep quality (Kakinami et al, 2017;Taylor et al, 2019). Further research is necessary in large populations to answer these questions.…”
Section: Clustering Of Health Risk Behaviorsmentioning
confidence: 99%
“…Homeless people sleep mostly > 10 h and present a low-level of physical activity. Simultaneously, although daily sleep longer than 9 h contributes to a higher risk of abdominal (visceral) obesity, it has not been linked directly with HDL cholesterol and triglycerides serum levels [ 24 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Participants ( N = 610) were recruited using flyers within each agency. Data from this survey were used previously to highlight the prevalence of modifiable health risk factors and investigated determinants of health among homeless adults living in Oklahoma City (Maness et al, 2019 ; Neisler et al, 2019 ; Taylor et al, 2019 ). Study eligibility requirements included: current homelessness, which was based on responses to questions related to the length of homelessness, place of current shelter, and reasons for homelessness.…”
Section: Methodsmentioning
confidence: 99%